2017
DOI: 10.1155/2017/8984713
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic Controller Design for Intelligent Robots

Abstract: This paper presents a fuzzy logic controller by which a robot can imitate biological behaviors such as avoiding obstacles or following walls. The proposed structure is implemented by integrating multiple ultrasonic sensors into a robot to collect data from a realworld environment. The decisions that govern the robot's behavior and autopilot navigation are driven by a field programmable gate array-(FPGA-) based fuzzy logic controller. The validity of the proposed controller was demonstrated by simulating three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
(19 reference statements)
0
6
0
1
Order By: Relevance
“…Traditional robotic control systems have been recently implemented for self-reconfigurable robots. For example, [ 157 ] uses a robust adaptive fuzzy controller to adapt a dynamic self-reconfigurable robot to different configurations without adjusting control parameters. Table A9 in Appendix H compares the main computational approaches for four categories of robots.…”
Section: Snn Embodiment Into Cognitive Robotic Systemsmentioning
confidence: 99%
“…Traditional robotic control systems have been recently implemented for self-reconfigurable robots. For example, [ 157 ] uses a robust adaptive fuzzy controller to adapt a dynamic self-reconfigurable robot to different configurations without adjusting control parameters. Table A9 in Appendix H compares the main computational approaches for four categories of robots.…”
Section: Snn Embodiment Into Cognitive Robotic Systemsmentioning
confidence: 99%
“…The tests showed that the suggested fuzzy logic worked satisfactorily. The control allowed the robot could display intelligent human behavior under complicated conditions [50]. As known that the great performances of conventional controllers cannot be accomplished if high non-linearity or uncertainty characterized the mechanisms to be regulated.…”
Section: Fuzzy Logic Controllersmentioning
confidence: 99%
“…One possible function on which adaptive control in mobile robot navigation tasks could be based is collision probability (CP) [35] since obstacle avoidance usually has the highest priority in the navigation stack hierarchy. The mediation can be implemented in several forms, and one of them is based on fuzzy set theory [36]. It is worth noting that several mediation engines can be used in the process, as well as several decision functions based on which the mediator infers the final decision and thus adapts the robot's behavior [18].…”
Section: Related Workmentioning
confidence: 99%